(untitled) (Research, Society and Development, 2025)
Trichloroacetic acid (TCA) is widely used in orofacial harmonization for skin texturization. Its application in chemical peels promotes deep exfoliation, improving wrinkles, acne scars, and hyperpigmentation. The aim of this narrative literature review is to present the use of TCA in skin texturization. This research is a narrative literature review, following the specifications of Rother (2007). Data collection was conducted in the PubMed, LILACS, and Scielo databases, using the following search terms: "Face," "Trichloroacetic Acid," and "Skin Abnormalities." Concentrations range from 10-35%, selected according to the patient’s skin condition. TCA offers a short recovery time and can be combined with other treatments for more comprehensive results. However, it is essential to follow specific care guidelines, such as avoiding sun exposure and using sunscreen, to ensure safety and effectiveness.